Tandem Self‐Powered Flexible Electrochromic Energy Supplier for Sustainable All‐Day Operations. Issue 30 (26th June 2022) - Huang, Jiaming; Ren, Zhiwei; Zhang, Yaokang; Fong, Patrick Wai‐Keung; Chandran, Hrisheekesh Thachoth; Liang, Qiong; Yao, Kuanming; Tang, Hua; Xia, Hao; Zhang, Hengkai; Yu, Xinge; Zheng, Zijian; et al.
Abstract: Self‐powered wearable energy suppliers are highly desirable for next‐generation smart electronic microsystems. However, it is still challenging to achieve an all‐day operating self‐powered energy device via the tandem integration strategy. Herein, a tandem self‐powered flexible energy supplier (SPFES) is proposed to "harvest and store" energy from sunlight (outdoor), dim‐light (indoor), and human body motion. In this novel device design, two flexible transparent electrodes are shared by three functional components: organic photovoltaic, triboelectric nanogenerator, and electrochromic supercapacitor. Interestingly, the SPFES shows distinctive in‐built features including energy indication, self‐modulation, and self‐protection. When compared to mechanically stacked devices, the SPFES avoids unnecessary encapsulation and external connections, resulting in a thinner device with a higher power‐to‐weight ratio (up to 110%). The concept of the SPFES paves an elegant route toward designing multi‐functional flexible energy‐harvest‐storage devices for all‐day operational wearable applications. Abstract : Herein, a novel tandem self‐powered flexible energy supplier (SPFES) is proposed to harvest and store energy from sunlight (outdoor), dim light (indoor), and human body motion. In this novel device design, two flexible transparent electrodes are shared by three functional components: organic photovoltaic, triboelectric nanogenerator, and electrochromic supercapacitor. The SPFES shows distinctive in‐built features including energy indication, self‐modulation, and self‐protection.